The labor situation in Japan and its analysis: Detailed exposition 2014/2015 - Japan Institute for Labour Policy and Training, Tokyo (Tokyo, 2015)
This publication is a compilation of write-ups describing individual themes related to the current status of labor issues in Japan. In principle, it is issued every year alternately as "General Overview" and "Detailed Exposition" editions. The former is aimed at providing basic information on the whole picture of labor issues and relevant labor policies in Japan, while the latter takes up contemporary topics and provides detailed exposition and analyses of their current trends."